Production Quality Control as An Important Factor to Meet Buyer Quality Standards at The Garment Company PT. Sukabumi Single Estuary - Wiyanti, Tuti; Lestari, Fitrina; Yoedani, Yoedani; Iskandar, Yusuf (Devotion : Journal of Research and Community Service, 2023)
The objectives of this study were achieved through the use of qualitative descriptive analysis, quantitative statistical ana-lysis, and quality control. To meet the quality target set by the Buyer, which is below 1.9%, it is necessary to know how many types of defects are found in the Finishing section and in the Final Inspection and how to reduce defects through the use of control strategies and methods applied by PT. Single Estuary. The data for this study comes from the statistics of production and damage to the Finishing department between May and August. Based on the findings of the study, it can be said that the implementation of quality control in this enterprise has been carried out quite successfully, with a noticeable improvement and a good quality improvement and is worthy of appreciation. These results show the seriousness or level of commitment of the management of PT. Muara Tunggal to continuously improve the quality according to the requests of buyers or buyers. The reduction in defects was first seen in early September 2022 with a defect rate of around 1.4%. Regarding the recommendations that can be made based on the findings, these include selecting raw materials according to Buyer's standards, hiring skilled labor, maintaining strict work ethics, providing training to employees to improve their skills, maintaining machines regularly, and improving neatness, comfort, and a safe workplace.